Design and Development of Finger-Printing Security Framework - Kalia, Surbhie (My University, 2007)
As the scale of networking increased, the threats and security concerns also multiplied. Network is a concept that started to exist after the standardization of the protocols and the RFCs. Once the Network analysis method and techniques were introduced since early 90’s, the security is under constant guard. Hence it’s important to know the current techniques used by both the administrators and attackers to identify the resources and system vulnerabilities posted on network. Remote OS Fingerprinting is a recent development on the Internet. The ability to remotely determine, with high accuracy, the Operating System of a remote host on the Internet is possible using tools and wide assortment of technologies. The implications of this technology are perhaps not yet fully understood; however, it is seen as enough of a threat that strategies are currently being developed to attain, analysis, deploy, prevent or spoof OS Fingerprinting. As the cause may call for the usage of fingerprinting is only understood once the data is collected and analyses.
Keywords: Fingerprinting Security; ISO-OSI Model; Network and Internet; Active Fingerprinting